Classrooms going online: Nordic lower secondary teachers' readiness at the COVID-19 outbreak - Marie Nilsberth; Anna Slotte; Tina Høegh; Sólveig Zophoníasdóttir; Jenny Högström; Annelie Johansson; Christina Olin-Scheller; Eva Tarander (University of Aberdeen, School of Education, 2021)
The aim of this article is to make visible Nordic lower secondary teachers' experiences of the initial period of the COVID-19 pandemic, guided by three research questions: 1. What challenges and strategies can be identified in teachers' descriptions of teaching during the pandemic outbreak? 2. What appears to be the role of digital technology in these challenges and strategies? 3. How can we understand the readiness and educational priorities of these Nordic schools in this time of crisis? Theoretically, we draw on the three main domains of purposes of education coined by Biesta (2015); qualification, socialisation and subjectification. The empirical data consists of online qualitative interviews with 17 lower secondary teachers from Denmark, Finland, Iceland and Sweden, teaching in different school subjects. A thematic content analysis was conducted, finding three main areas of challenges in relation to organisation of teaching, classroom dialogue and assessment of student learning. Our analysis makes visible how besides digital readiness, the readiness of the studied schools relied on the teachers' ability to act independently in finding professional solutions in a time of crisis. The teachers did not just sit and wait for instructions on what to do, but took initiatives and managed the situation as best as they could drawing on their professional competence.